Ideal Legal Protection Policy for Well-Known Trademark to Support Investment Climate in Indonesia - Setiawan, Purwanto (Global Legal Review, 2025)
An ideal legal protection policy for well-known trademarks is crucial to support the investment climate in Indonesia. As a country based on law and welfare, Indonesia aims to provide legal protection and guarantees in various economic activities. Trademarks are essential in attracting foreign direct investment (FDI), and thus, legal certainty and justice for well-known trademark holders are of utmost importance. However, problems arise from trademark violations that can potentially hinder FDI. The objective of this research is to identify and propose an ideal legal regulatory framework that ensures legal certainty and justice for well-known trademarks investing in Indonesia. The research examines three main issues: the aspects of legal certainty and justice in the current regulations, the challenges found in their implementation, and how these regulations can be made more legally certain and just to foster a conducive investment climate. Using a normative legal research method with empirical support, the study analyzes secondary data, including policies, legal rules, and court decisions related to trademark law in Indonesia. This descriptive research explains the guarantees of legal certainty and justice for well-known trademark holders in Indonesia. The findings indicate that while Indonesia’s trademark law (Law Number 20 of 2016) provides legal certainty through registration and enforcement, several issues hinder effective protection. These problems include the absence of philosophical requirements, a dual understanding of the law, complex three-dimensional trademark provisions, a low legal culture among the public, disharmony in regulations, weak law enforcement, and abstract trademark criteria. Therefore, the ideal protection for well-known trademarks in Indonesia should incorporate philosophical requirements, align with international standards, provide adequate protection, ensure an efficient and transparent registration process, and foster international cooperation.